Biobanks in oncology: global experience and Russian reality - Andrei D. Kaprin (IP Habib O.N., 2020)
One of the integral components of modern large-scale research projects in the field of medicine are biobanks. The main objective of this infrastructure is the professional collection of biological samples that can be studied with respect to a wide range of molecular biological parameters and will not lose their information value over a long storage period. These samples are made informative not only by correctly conducted preanalytical preparation at the stage of taking samples and placing them in storage, but also by detailed information support (the so-called annotated samples). The sample annotation is the fully collected personal, clinical and laboratory data about a patient. An important point of the biobank infrastructure is compliance with regulatory legal acts and ethical standards, including the procedure for signing an informed consent by a patient about voluntary donation of biological samples and the use of personal data. All this ensures the implementation of the main objective of creating biobanks the wide and uninterrupted availability of collections of biological material for researchers and developers and compliance with specific scientific tasks. This review is devoted to biobanking issues, as well as to the description and analysis of the currently existing oncological biobank infrastructure, both globally and within the Russian Federation.